2014
DOI: 10.1111/imj.12448
|View full text |Cite
|
Sign up to set email alerts
|

New oral anticoagulants: a practical guide on prescription, laboratory testing and peri‐procedural/bleeding management

Abstract: New oral anticoagulants (NOAC) are becoming available as alternatives to warfarin to prevent systemic embolism in patients with non-valvular atrial fibrillation and for the treatment and prevention of venous thromboembolism. An in-depth understanding of their pharmacology is invaluable for appropriate prescription and optimal management of patients receiving these drugs should unexpected complications (such as bleeding) occur, or the patient requires urgent surgery. The Australasian Society of Thrombosis and H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
138
1
2

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 143 publications
(144 citation statements)
references
References 38 publications
3
138
1
2
Order By: Relevance
“…3 In case an anti-Xa assay is not accessible, several authors have outlined alternative strategies to estimate the intensity of anticoagulation in rivaroxaban-treated patients based on routine coagulation testing. Although a normal PT does not rule out the presence of rivaroxaban, 4,18,22 it has been suggested that intact hemostasis can be expected. 23 Normal PT values measured with sensitive reagents are probably sufficient to expect acceptable coagulation in case of urgent surgery.…”
Section: Coagulation Testing In Rivaroxaban-treated Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 In case an anti-Xa assay is not accessible, several authors have outlined alternative strategies to estimate the intensity of anticoagulation in rivaroxaban-treated patients based on routine coagulation testing. Although a normal PT does not rule out the presence of rivaroxaban, 4,18,22 it has been suggested that intact hemostasis can be expected. 23 Normal PT values measured with sensitive reagents are probably sufficient to expect acceptable coagulation in case of urgent surgery.…”
Section: Coagulation Testing In Rivaroxaban-treated Patientsmentioning
confidence: 99%
“…23 Normal PT values measured with sensitive reagents are probably sufficient to expect acceptable coagulation in case of urgent surgery. 22 Furthermore, thrombolysis for ischemic stroke may be considered in patients on rivaroxaban if PT and aPTT are normal after individual risk assessment. 2,24 However, NOACspecific sensitivity varies between test reagents, and general recommendations are therefore problematic.…”
Section: Coagulation Testing In Rivaroxaban-treated Patientsmentioning
confidence: 99%
“…factor VIII inhibitor bypass activity (FEIBA), or recombinant factor VIIa (rVIIa) as well as antifibrinolytic therapy (tranexamic acid) can be used . Renal replacement therapy should be considered for dabigatran which is dialyzable [42][43][44][45][46].…”
Section: How Can We Manage Bleeding With Odi?mentioning
confidence: 99%
“…While the direct oral anticoagulants do demonstrate lower risk for intracranial hemorrhage, both major and non-major bleeding events have been reported in patients receiving these medications [11,12], and their management remains a cause of major concern [13]. Until now, most of the data on DOAC therapy is derived from clinical trials with limited postmarketing evaluations, and the focus has been on the comparison of bleeding risk between DOAC therapy and warfarin [14,15].…”
Section: Introductionmentioning
confidence: 99%